1986
DOI: 10.1073/pnas.83.3.654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the external pH on Ca channels: experimental studies and theoretical considerations using a two-site, two-ion model.

Abstract: Some effects of the external pH on Ca channels were studied in a hybridoma cell line (mAb-7B), by using the whole-cell configuration of the patch-clamp technique. As the pH was lowered, both the activation and the inactivation curves shifted toward less negative membrane potentials, suggesting a pH-induced decrease of an external negative surface potential, sensed by the mechanism of gating. The potential for half-activation, V1/2, and that for half-inactivation, Vh, were related by a straight line with a slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 7 publications
3
54
2
Order By: Relevance
“…Furthermore, increases in current upon alkalization are not unique to cardiac Ca channels. Iijima et al (1986) have reported the same observation for Ca channels in a mouse hybridoma cell line and Hille et al (1975) found the same effect for Na channels. Presumably there is a site that is only partially titrated at pH 7.4.…”
Section: Relationship To Previous Work M Noncardiac Preparationssupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, increases in current upon alkalization are not unique to cardiac Ca channels. Iijima et al (1986) have reported the same observation for Ca channels in a mouse hybridoma cell line and Hille et al (1975) found the same effect for Na channels. Presumably there is a site that is only partially titrated at pH 7.4.…”
Section: Relationship To Previous Work M Noncardiac Preparationssupporting
confidence: 59%
“…A recent study by Iijima et al (1986) investigated the effects of extracellular H ions on Ca currents in a mouse hybridoma cell line. They came to the conclusion that gating shifts and surface concentration changes were responsible for the increase or decrease of the Ca current magnitude as a function of pHo.…”
Section: Mechanisms Of H Ion Modulation Of Heart Ca Channelsmentioning
confidence: 99%
“…Among these, the low threshold channels may have been partially inhibited by benzolamide (Gottfried and Chesler, 1995), but, in the somata and proximal dendrites, high threshold Ca 2ϩ channels would predominate (Christie et al, 1995;Magee and Johnston, 1995). There is evidence that a small rise in pH e can enhance high threshold Ca 2ϩ currents (Iijima et al, 1986;Barnes and Bui, 1991;Chen et al, 1996;Tombaugh and Somjen, 1996). It is therefore plausible that benzolamide, by increasing the alkaline transients, may have augmented Ca 2ϩ influx through both NMDARs and voltage-gated Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…These Ca 2ϩ channels could be involved because of their own sensitivity to external pH (Iijima et al, 1986;Barnes and Bui, 1991;Chen et al, 1996) or because of depolarization-mediated, mutually reinforcing interactions with NMDARs.…”
Section: Discussionmentioning
confidence: 99%
“…L-type Ca 2ϩ channels are sensitive to extracellular pH near the physiological range (Iijima et al, 1986;Barnes and Bui, 1991;Chen et al, 1996) and might therefore be influenced by the enhanced buffering caused by XCA. With the L-type channel antagonist D-600 in the patch pipette (Schiller, 2004), there was no effect on the baseline ADP, and the addition of XCA still caused a significant curtailment of the ADP in seven cells.…”
Section: The Effect Of Xca On Responses In Current Clampmentioning
confidence: 99%